College Students with Inflammatory Bowel Disease: A Qualitative Study of Challenges Associated with College Transition and Self-Care (Mary Ann Liebert, 2020)
Introduction: The social impact of inflammatory bowel disease (IBD) on student transition to college is significant, yet poorly understood. Methods: Two 90-min focus groups (FGs) were conducted with eight student-patients with IBD. Reflective journals were used to corroborate, elaborate, or challenge emergent FG findings. Results: Six themes emerged: (1) transitioning to college, (2) interacting with physicians, (3) affecting social life, (4) managing the disease by yourself and through support, (5) coping strategies, and (6) facing disease challenges. These themes remained relevant in the reflective writings. Analysis of serial journal entries showed that students' social life and engagement in coursework was affected 66% and 54% of the time, respectively. Conclusion: Our findings offer guidance for improving students' college success, quality of care, and enhancing physician?patient interactions. Students with IBD have a disability that may not be obvious or visible. They require specific support to help them transition and succeed in college.